The excavation of Bankhead homestead, Darvel, Ayrshire. Issue 1 (March 2019) - Hendry, Alastair
Abstract : The excavation at Bankhead Farm, Darvel, tested (a) the local tradition of the existence of a stone castle on site and (b) the undocumented story that the local archaeological society had excavated the site in the 1920's. The castle story was disproved but more than one third of the site had clearly been disturbed. The untouched area revealed the foundation trenches of two palisaded roundhouses, one of which yielded Roman pottery of Antonine date.